Characterization of the Points of ϕ-Strong Summability of Fourier–Laplace Series for Functions of the Class L_p(S^m), p > 1 - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider the behavior of the ϕ-strong means of Fourier–Laplace series for functions that belong to L_p(S^m), p > 1, on a set of points of full measure on an m-dimensional sphere S^m.